Mechanism and Origins of Ligand‐Controlled Selectivity of Rhodium‐Catalyzed Intermolecular Cycloadditions of Vinylaziridines with Alkynes. Issue 15 (27th June 2016) - Zhang, Xinwen; Zou, Hongyan; Huang, Genping
Abstract: In this report, the mechanism of the rhodium‐catalyzed intermolecular cycloaddition of vinylaziridines with alkynes is investigated by means of density functional theory calculations. The calculations show that the reaction is initiated by a C−N oxidative addition to form the Rh–allyl complex, from which the migratory insertion of the alkyne into the Rh−N bond was found to take place in a 1, 2‐fashion. The subsequent competing direct C−C reductive elimination and alkenyl isomerization/ C−C reductive elimination led to the [3+2] and [5+2] cycloadditions, respectively. The experimentally observed ligand‐controlled selectivity is reproduced quite well by the calculations. Importantly, it turns out that the steric repulsion between the ligand and the alkenyl moiety has a profound impact on the direct C−C reductive elimination and the alkenyl isomerization, which enables the selectivity switch between the [3+2] and [5+2] cycloaddition upon change of ligand. Abstract : [3+2] versus [5+2] cycloaddition : The rhodium‐catalyzed intermolecular cycloadditions of vinylaziridines with alkynes were investigated by means of DFT calculations to establish the detailed reaction mechanism and elucidate the origins of the ligand‐controlled [3+2] versus [5+2] cycloaddition.